An improved multi-velocity cellular automaton model that considers psychological impatience - Hongpeng Qiu; Wenke Zhang; Meng Shi; Eric Wai Ming Lee (Journal of Safety Science and Resilience, 2025)
The cellular automaton (CA) model is an essential tool for studying pedestrian evacuation dynamics; moreover, improving simulations of actual evacuation environments and increasing the reliability of evacuation data are important problems for researchers. The complex psychological dynamics of pedestrians during evacuation and the evacuation velocities are essential components of such models. This study proposes and verifies a synchronously updated multi-velocity evacuation impatient CA model with a corresponding time correction formula. Our model that considers pedestrians’ psychological impatience can simulate complex scenarios in which different pedestrians simultaneously evacuate at different speeds. In addition, our model accurately simulates and reproduces the phenomena found in actual experiments: as the self-growth parameter of impatience increases, the evacuation efficiency first increases and then decreases, and as the contagion parameter of impatience increases, the evacuation efficiency decreases. The time correction method and formula are critical for obtaining reliable results from simulations in which pedestrians evacuate at various speeds, and they are expected to be indispensable parts of multi-velocity CA models for predicting complex evacuation scenes.